Extraction and encapsulation of capsaicinoids of red pepper oleoresin - Bibi Marzieh Razavizadeh; Rasoul Kadkhodaee; Zeinab Zaferani (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2015)
Pepper oleoresin is dense oil and/ or semi-solid extract that is used as a flavoring and coloring agent in various food products. Spicy taste of red pepper oleoresin is due to a group of alkaloids called capsaicinoids. In this study for the first step, red pepper oleoresin was extracted using ethanol, methanol and 2-propanol as extraction solvents. In the second step, extracted capsaicinoids were encapsulated with Arabic gum and whey protein concentrate (WPC) as ingredient wall material  applying spray drying method. The statistical results showed the type of solvent had a significant effect on the efficiency of the extraction, while for the ratio of powder to solvent no significant differences in the efficiency of extraction was observed. The effect of composition of wall material (5, 10 and 15 %) and blending ratio polymeric matrix of gum Arabic and WPC (in the ratio of 100:0, 1: 1, and 0:100) on the size of the powder containing encapsulated capsaicinoids as well as encapsulated efficiency were evaluated. It was observed that the composition of wall material and blending ratio of polymeric matrix affected the mean diameter, particle size distribution, and specific surface area. That is to say, the retention time of active ingredients in gum Arabic was more than WPC. In addition, the encapsulation efficiency and remaining of capsaicinoids in the capsule increased as the wall material concentration increased from 5 to 15 percentages.